Urban expansion analysis using landsat images in Penang, Malaysia - Tew, Yi Lin; Tan, Mou Leong; Narimah Samat,; Yang, XiaoYing (Penerbit Universiti Kebangsaan Malaysia, 2019)
Urban expansion mapping is important in urban planning, land use and water resources management. The purpose of this study is to evaluate the spatio-temporal trends of urban expansion in Penang using three Landsat satellite images taken in 2004, 2011 and 2018. Maximum Likelihood was used to classify the land uses into urban, agricultural, water, and forest. Comparison of the classified images with time-series Google Earth images and field data collection resulting an accuracy up to 90%. The results showed that urban have been expanded around 5% from 2004 to 2018. Major urban development is mainly found in the eastern part of Penang island. Meanwhile, major development in the Penang mainland can be found in the middle and western regions. Due to the limited development land on the Penang Island, a rapid urban expansion can be found in the south-western part of the Penang mainland that near to the second bridge. In order to maintain the city and community sustainability in Penang, government needs to plan on balanced socio-economic growth for the near future.